Hypercyclic operators on Lipschitz spaces - M. V. Dubey; Z. H. Mozhyrovska; A. V. Zagorodnyuk (Математичні Студії)
We consider hypercyclic operators on free Banach spaces and little Lipschitz spaces which are some kind of generalizations of shift operators and composition operators respectively.